Altered relationship between prefrontal glutamate and activation during cognitive control in people with high trait anxiety. (August 2019) - Morgenroth, Elenor; Orlov, Natasza; Lythgoe, David J.; Stone, James M.; Barker, Holly; Munro, James; Eysenck, Michael; Allen, Paul
Abstract: Trait anxiety can affect cognitive control resulting in ineffective and/or inefficient task performance. Moreover, previous functional Magnetic Resonance Imaging (fMRI) studies have reported altered dorsolateral prefrontal cortex (DLPFC) activity in anxious cohorts, particularly when executive control is required. Recently, it has been demonstrated that cortical glutamate levels can predict both functional activation during cognitive control, and anxiety levels. In the present study we sought to investigate the relationship between trait anxiety, prefrontal glutamate levels and functional activation in DLPFC during a cognitive control task. Thirty-nine participants assigned to either low trait anxiety (LTA) or high trait anxiety (HTA) groups underwent 1 H-Magnetic Resonance Spectroscopy ( 1 H-MRS) to measure levels of resting glutamate in the prefrontal cortex (PFC). Participants also completed fMRI during a Stroop task comprising congruent and incongruent colour word trials. The HTA group showed reduced task performance relative to the LTA group. In the LTA group, there was a positive association between PFC Glu levels and DLPFC activation during incongruent trials. This association was absent in the HTA group. Individual differences in trait anxiety affect the relationship between PFC glutamate levels and DLPFC activation, possibly contributing to ineffective task performance when cognitive control is required.